Targeting ceramide transfer protein sensitizes AML to FLT3 inhibitors via a GRP78-ATF6-CHOP axis - Xiaofan Sun; Yue Li; Juan Du; Fangshu Liu; Caiping Wu; Weihao Xiao; Guopan Yu; Xiaowei Chen; Robert Peter Gale; Hui Zeng (Nature Communications)
Abstract Sphingolipid, ceramide for example, plays an essential role in regulating cancer cell death. Defects in the generation and metabolism of ceramide in cancer cells contribute to tumor cell survival and resistance to chemotherapy. Ceramide Transfer Protein (CERT) determines the ratio of ceramide and sphingomyelin in cells. Targeting CERT sensitizes solid cancer cells to chemotherapy. However, whether targeting CERT to induce ceramide accumulation thereby improving AML therapy efficiency remains elusive. Here, we show that knocking down CERT inhibits the growth and promotes the apoptosis of AML cells carrying FLT3-ITD mutation. Combining CERT inhibitor with FLT3 inhibitor exhibits synergistic effects on FLT3-ITD mutated acute myeloid leukemia (AML) cells. Additionally, co-treatment of HPA-12 and Crenolanib is effective in FLT3-ITD+ and FLT3-TKD+ AML patients. The synergistic effects are found to be mediated by the endoplasmic reticulum stress-GRP78/ATF6/CHOP axis and mitophagy. Our data provide an effective strategy to enhance the efficacy of FLT3 inhibitors in AML.